Variations in chlorophyll content, stomatal conductance, and photosynthesis in Setaria EMS mutants - Chan-juan TANG; Ming-zhao LUO; Shuo ZHANG; Guan-qing JIA; Sha TANG; Yan-chao JIA; Hui ZHI; Xian-min DIAO (Journal of Integrative Agriculture, 2023)
Chlorophyll (Chl) content, especially Chl b content, and stomatal conductance (Gs) are the key factors affecting the net photosynthetic rate (Pn). Setaria italica, a diploid C4 panicoid species with a simple genome and high transformation efficiency, has been widely accepted as a model in photosynthesis and drought-tolerance research. The current study characterized Chl content, Gs, and Pn of 48 Setaria mutants induced by ethyl methanesulfonate. A total of 24, 34, and 35 mutants had significant variations in Chl content, Gs, and Pn, respectively. Correlation analysis showed a positive correlation between increased Gs and increased Pn, and a weak correlation between decreased Chl b content and decreased Pn was also found. Remarkably, two mutants behaved with significantly decreased Chl b content but increased Pn compared to Yugu 1. Seven mutants behaved with significantly decreased Gs but did not decrease Pn compared to Yugu 1. The current study thus identified various genetic lines, further exploration of which would be beneficial to elucidate the relationship between Chl content, Gs, and Pn and the mechanism underlying why C4 species are efficient at photosynthesis and water saving.